The Project Method e-course: the use of tools towards the evolution of the Greek teachers' online community. (14th January 2008) - Vivitsou, Marianna; Lambropoulos, Niki; Konetas, Dimitris; Paraskevas, Michael; , Evangelos Grigoropoulos
The second web generation (Web 2.0) opens up new perspectives for community building through communication and collaboration. Open Source Software (OSS) have contributed to the viability of educational courses and extended the potential of online learning. Yet, if the aim is to provide users with a dynamic context allowing collective intelligence to emerge, not only is the development of appropriate learning environments required but also the integration of a flexible pedagogical scenario. For the purposes of this paper, the authors focus on a pilot e-course implemented on the Greek teachers' national intranet e-learning platform aiming to provide evidence that the transition from an information retrieval situation to a social learning situation requires the mediation of improved OS systems. In these, design should aim for the encouragement of the users' cognitive and social presence so that knowledge can be constructed through collaboration and critical reflection within an active online community.